Psychosocial predictors in upper-extremity vascularized composite allotransplantation: A qualitative study of multidimensional experiences including patients, healthcare professionals, and close relatives - Hummel, Nikolas R.; Zuo, Kevin J.; Talbot, Simon; Zimmerman, Zoe E.; Katz, Jeffrey N.; Kinsley, Sarah E.; Kumnig, Martin (Frontiers in Psychology, 2023)
Background: The impact of patient specific psychosocial factors on functional out-comes after upper extremity (UE) vascularized composite allotransplantation (VCA) is poorly understood. The objective of this study was to identify relevant psychosocial predictors for success or failure of UE VCA in an Austrian cohort. Methods: A qualitative study was undertaken consisting of semistructured interviews with UE VCA staff, transplanted patients, and close relatives. Participants were asked about their perceptions of factors that either favored or hindered a successful transplant outcome, including functional status before surgery, preparation for transplant, decision-making, reha-bilitation and functional outcome after surgery, and family and social support. Interviews were conducted online and recorded with the consent of interviewees. Results: Four bilateral UE VCA patients, 7 health care professionals, and a sister of a patient participated in the study. Thematic analysis revealed the importance of an expert in-terdisciplinary team with adequate resources for patient selection. Psychosocial aspects of prospective candidates are crucial to evaluate as they contribute to success. Both patients and providers may be impacted by public perceptions of UE VCA. Functional outcomes are opti-mized with a life-long commitment to rehabilitation as well as close, ongoing provider in-volvement Conclusions: Psychosocial factors are important elements in the assessment and fol-low-up care for UE VCA. To best capture psychosocial elements of care, protocols much be individualized, patient-centered, and interdisciplinary. Investigating psychosocial predictors and collecting outcomes is, thus, critical to justifying UE VCA as a medical intervention and to providing accurate and salient information to prospective candidates.